Get the most out of your questions with IDNLearn.com's extensive resources. Our experts provide prompt and accurate answers to help you make informed decisions on any topic.
Sagot :
[tex]-3x = -5y -8~~~....(i) \\\\6x -3y = -5 ~~......(ii)\\\\\text{Multiply equation (i) by 2 and do (i) + (ii):}\\\\2 \cdot (-3x) + 6x -3y = 2(-5y-8) + (-5)\\\\\implies -6x +6x -3y = -10y -16 -5 \\\\\implies -3y = -10y -21\\\\\implies -3y +10y =-21\\\\\implies 7y = -21 \\\\\implies y = -\dfrac{21} 7 = -3\\\\\text{Substitute}~y =-3~ \text{in equation (ii):} \\\\6x - 3(-3) = -5\\\\\implies 6x +9 = -5\\\\\implies 6x = -5 -9 = -14\\\\\implies x = -\dfrac{14}6 = - \dfrac{7}3\\[/tex]
[tex]\text{Hence}~ (x,y) = \left(-\dfrac 73, -3 \right)[/tex]
Thank you for contributing to our discussion. Don't forget to check back for new answers. Keep asking, answering, and sharing useful information. Discover insightful answers at IDNLearn.com. We appreciate your visit and look forward to assisting you again.